1994
DOI: 10.1002/pro.5560030507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structures and the crystal contacts of trypanosomal triosephosphate isomerase in four different crystal forms

Abstract: Triosephosphate isomerase (TIM) is a dimeric enzyme consisting of 2 identical subunits. Trypanosoma1 TIM can be crystallized in 4 different spacegroups: P212121, C2(big cell), C2(small cell), and P1. The P1 crystal form only grows in the presence of 1.4 M DMSO; there are 2 DMSO binding sites per subunit. The structures have been refined at a resolution of 1.83 A, 2.10 A, 2.13 A, and 1.80 A, respectively. In the 4 different spacegroups the TIM subunit can be observed in the context of 7 different crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…Based on the observation that crystal structures of identical proteins can contain residues in different rotamer positions (Faber & Matthews, 1990;Kossiakoff et al, 1992;Kishan et al, 1994), we attempted to measure the amount of variability for different residue types in proteins that had been solved in different crystal structures. This would put an upper limit on the accuracy that any sidechain prediction program could hope to achieve.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observation that crystal structures of identical proteins can contain residues in different rotamer positions (Faber & Matthews, 1990;Kossiakoff et al, 1992;Kishan et al, 1994), we attempted to measure the amount of variability for different residue types in proteins that had been solved in different crystal structures. This would put an upper limit on the accuracy that any sidechain prediction program could hope to achieve.…”
Section: Resultsmentioning
confidence: 99%
“…In that structure, each TIM subunit had two equivalent DMSO-binding sites. 56 Neither of those two DMSO-binding sites were observed in our A1 structure. DMSO is an organic solvent that lowers the bulk dielectric constant of the solvent through hydrogen bonding to water molecules.…”
Section: The Role Of Dmsomentioning
confidence: 86%
“…26 Secondary structural elements involved in lattice contacts have not previously been documented for a large set of proteins. A study of four different forms of trypanosomal triosephosphate isomerase revealed that 77% of the residues that were involved in crystal contacts were found in ''loop'' regions, 6 which is probably equivalent to combined coil and turn regions by the definition of Kabsch and Sander. 52 This percentage is clearly much higher than average (Table III).…”
Section: Secondary Structurementioning
confidence: 99%